Cartilla didáctica como material pedagógico para el fortalecimiento de las competencias lectoras. (2020)
This work starts from the presentation of the knowledge pro tests, in eleventh grade students at the San Agustín IED educational institution, based on a diagnosis in reading skills, the creation of a primer is proposed to strengthen them from, the following text structures: microstructures, macro structures and superstructures, which the ICFES takes up for the creation of the section Critical reading.